S4.2 Introduction of rapid syphilis testing strengthens health systems and health worker capacity to provide integrated PMTCT services. (10th July 2011) - Strasser, S; Chintu, N; Sripipatana, T; Shelley, K; Musana, O; Phiri, A; Ncube, A T; Gill, M; Hoffman, H; Bitarakwate, E
Abstract : Background: In partnership with Ministries of Health of Uganda and Zambia, we piloted the introduction of rapid syphilis testing (SD Bioline) in large scale PMTCT programs. Both countries provide PMTCT services within integrated maternal newborn child health programs. Point of care (PoC) testing for HIV, malaria and haemoglobin are routine. While Uganda did not have routine access to syphilis testing prior to the study, Zambia was using RPR as part of the standard package of antenatal care (ANC) services although access was inconsistent and not available in remote clinics. Methods: A mixed method study using both qualitative and quantitative indicators was used to assess acceptability, feasibility and affordability of the rapid syphilis testing. Ongoing engagement of Ministries of Health and clinic staff was used to assess health system ability to integrate rapid syphilis testing within PMTCT programs. Results: The use of rapid syphilis testing in ANC was acceptable, feasible and cost effective see Abstract S4.2 table1 with statistically significant increases in same day testing and treatment and high levels of healthcare worker satisfaction as reported elsewhere (IAS, 2011). This study has resulted in measurable improvements to the health system including: the development of robust internal and external laboratory quality assurance (QA) systems and an integrated training for health workers on congenital syphilis prevention, treatment and quality assured use of PoC technologies. Use of integrated registers in MCH for data collection allowed for seamless initiation of the service into ANC. Supply chain systems were developed and enhanced especially in Uganda where syphilis testing was previously not routine. 13 131 women in Uganda and 12 761 women in Zambia received syphilis testing during the 5 month study period with a significant number of tests successfully carried out by nurse/midwives. Integrating syphilis and HIV supply chains led to reduced days of stock out of HIV test kits due to better ordering practices in some sites and did not negatively impact or integration significantly improved HIV service uptake. Conclusions: In addition to being acceptable, feasible and affordable, the systematic introduction of a PoC diagnostic for syphilis can lead to wider health system improvements and enhanced HIV service uptake in ANC. Wider use of PoC technologies is encouraged.